Strengthening the inner circle: the marriage networks of elite families in Joseon Korea - Hong, Eunbin; Lee, Sangkuk; Yoo, Jane (History of the Family, 2021)
Socioeconomic homogamy is a prominent process for reproducing the social structure in preindustrial societies including East Asian countries. Although Joseon Korea was a centralized bureaucratic state under a king, the stratification system was unique by its ambiguity such that the previlege of an upper class was not officially confirmed. Since the social status was rather conferred by the reputation of the family, the quality of marriage relation was important for a man to be ranked as a central official. In this paper, we investigate patterns of social homogamy among elite families in the early Joseon Korea through empirical evidence of the relationship between official rank and spousal family background. We created a novel dataset by compiling the marriage network and official rank information of 14,508 individuals from the jokbos (族譜, genealogy) of 15 elite families and conduct an ordinal logit regression analysis to investigate whether spousal family background increases the probability of an individual being promoted in the bureaucracy. We find that the socio-political power of affinal kin has a greater effect on promotions than the descent and meritocratic effects. Particularly, the empirical evidence shows that marrying into a queen consort’s family increased the likelihood of an individual being ranked in a high position, which was beneficial for retaining the political power of him and the family. The study shows that marriage as a means of managing the socio-political inner circle of elite families, shaping the elites’ socio-political inner circle, built on the marriage network around a queen consort’s family to benefit the royal authority and the elite group.
Keywords: elite families; jokbo; Joseon Korea; marriage relationship; official rank; queen consort